Statistical Diagnostic for Partially Linear Varying Coefficient Model with Random Right Censorship Based on Empirical Likelihood Method - Wang Shuling; Liao Daqing; Liu Man (International Journal of Analysis and Applications, 2013)
In this paper, the empirical likelihood method to study the statistical diagnostic for partially linear varying coefficient model with random right censorship. First the primary model is transformed to patially linear varying coefficient model; then the parameter estimation equation based on the experience of application of likelihood methods to estimate. Experience based on the deletion model proposed experience like natural Cook distance, likelihood distance, then find outliers and strong influence point; At last, an example is given to illustrate our results.